Similar CD4/CD8 Ratio Recovery After Initiation of Dolutegravir Plus Lamivudine Versus Dolutegravir or Bictegravir-Based Three-Drug Regimens in Naive Adults With HIV - Martínez-Sanz, Javier; Ron, Raquel; Moreno, Elena; Sánchez-Conde, Matilde; Muriel, Alfonso; López Cortés, Luis Fernando; Blanco, José Ramón; Pineda, Juan Antonio; Mena, Álvaro; Calzado Isbert, Sonia; Moreno, Santiago; Serrano-Villar, Sergio (Frontiers in Immunology, 2022)
Background The initiation of antiretroviral treatment based on a two-drug regimen (2DR) with dolutegravir plus lamivudine has demonstrated non-inferior efficacy than dolutegravir-based three-drug regimens (3DR). We aim to assess whether the treatment initiation with this 2DR has a different impact on the CD4/CD8 ratio recovery than INSTI-based 3DR. Methods We emulated a target trial using observational data from the Spanish HIV Research Network cohort (CoRIS). The outcomes of interest were the normalization of the CD4/CD8 ratio at 48 weeks using three different cutoffs: 0.5, 1.0, and 1.5. We matched each participant who started 2DR with up to four participants who received 3DR. Subsequently, we fitted generalized estimating equation (GEE) models and used the Kaplan–Meier method for survival curves. Results We included 485, 805, and 924 participants for cutoffs of 0.5, 1.0, and 1.5, respectively. At 48 weeks, 45% of participants achieved a CD4/CD8 ratio >0.5, 15% achieved a ratio >1.0, and 6% achieved a ratio >1.5. GEE models yielded a similar risk of reaching a CD4/CD8 ratio >0.5 (OR 1.00, 95% CI 0.67 - 1.50), CD4/CD8 >1.0 (OR 1.03, 95% CI 0.68 - 1.58), and CD4/CD8 >1.5 (OR 0.86, 95% CI 0.48 - 1.54) between both treatment strategies. There were no differences between 2DR and 3DR in the incidence ratio of CD4/CD8 ratio normalization at 0.5, 1.0 and 1.5 cut-offs. Conclusions In this large cohort study in people with HIV, ART initiation with dolutegravir plus lamivudine vs. dolutegravir or bictegravir-based triple antiretroviral therapy showed no difference in the rates of CD4/CD8 normalization at 48 weeks.